Nanopore arrays in a silicon membrane for parallel single-molecule detection: DNA translocation. (16th July 2015) - Zhang, Miao; Schmidt, Torsten; Jemt, Anders; Sahlén, Pelin; Sychugov, Ilya; Lundeberg, Joakim; Linnros, Jan
Abstract: Optical nanopore sensing offers great potential in single-molecule detection, genotyping, or DNA sequencing for high-throughput applications. However, one of the bottle-necks for fluorophore-based biomolecule sensing is the lack of an optically optimized membrane with a large array of nanopores, which has large pore-to-pore distance, small variation in pore size and low background photoluminescence (PL). Here, we demonstrate parallel detection of single-fluorophore-labeled DNA strands (450 bps) translocating through an array of silicon nanopores that fulfills the above-mentioned requirements for optical sensing. The nanopore array was fabricated using electron beam lithography and anisotropic etching followed by electrochemical etching resulting in pore diameters down to ∼7 nm. The DNA translocation measurements were performed in a conventional wide-field microscope tailored for effective background PL control. The individual nanopore diameter was found to have a substantial effect on the translocation velocity, where smaller openings slow the translocation enough for the event to be clearly detectable in the fluorescence. Our results demonstrate that a uniform silicon nanopore array combined with wide-field optical detection is a promising alternative with which to realize massively-parallel single-molecule detection.